From Near to Far: Maria Short and the Places and Spaces of Science in Edinburgh from 1736 to 1850 - Loader, Alison Reiko (Teorie vědy / Theory of Science, 2014)
From Near to Far: Maria Short and the Places and Spaces of Science in Edinburgh from 1736 to 1850 Abstract: A relatively unknown woman named Maria Theresa Short opened a popular observatory in 1835 in Ed inburgh - a time and place where men of science and property had long failed to make a viable space for astronomy. She exhibited scientific instruments to a general public, along with a great telescope and a walk-in camera obscura that projected live views of the city and continues to delight audiences to this day. To better understand Short’s accomplishments, achieved as scientific and public life became increasingly closed to women, this study explores her largely untold story, and maps some of the places of science around it. Finding local contingencies, multiple sites and practices by diverse groups, it proposes that tensions within the connections between science and spectacle and the use of popularization to promote its professionalization produced gaps that even a marginal figure like Maria Short could inhabit and exploit. Keywords: camera obscura; observatory history; optical instruments; popularization; professionalization; University of Edinburgh; women and science Zblízka do dáli: Maria Short a místa a prostory vědy v Edinburghu v letech 1736 až 1850 Abstrakt: Relativně neznámá žena jménem Maria Theresa Short otevřela roku 1835 v Ediburghu lidovou hvězdárnu - v době a v místě, kde mužové vědy a majetku dlouho selhávali při vytváření životaschopného proctor pro astronomii. Short vystavovala pro široké publikum vědecké nástroje a také velký dalekohled i camera obscuru, do níž šlo vejít a pozorovat živoucí dění ve městě a která poskytuje divákům zážitky dodnes. Abychom lépe porozuměli úspěchům, jichž Short dosáhla, zatímco se vědecký a veřejný život ženám výraz- něji uzavíral, tato studie probádává její z větší části nevyřčený příběh a kolem něj mapuje některá z míst vědy. Na základě nalezení lokálních podmíněností, vícenásobných míst a praktik různých skupin, tato studie přichází s propozicí, že napětí vznikající ze spojení vědy a spektáklu a z užití popularizace k podpoře profesionalizace vytvářelo mezery, které mohla i marginální osobnost jako Maria Short obsadit a využívat jich. Klíčová slova: camera obscura; dějiny observatoří; optické nástroje; popularizace; profesionalizace; Univerzita v Edinburghu; ženy a věda